Power electronic systems walsh analysis with MATLAB® - Deb, Anīśa; Ghosh, Suchismita (CRC Press/Taylor & Francis Group, 2014)
This text builds a case for Walsh analysis as a powerful tool in the study of power electronic systems. It considers the application of Walsh functions in analyzing power electronic systems, and the advantages offered by Walsh domain analysis of power electronic systems. Solves Power Electronic Systems in an Unconventional Way. This book successfully integrates power electronics as well as systems and control. Incorporating a complete orthonormal function set very much unlike the sine cosine functions, it introduces a blending between piecewise constant orthogonal functions and power electronic systems. It explores the background and evolution of power electronics, and discusses Walsh and related orthogonal basis functions. It develops the mathematical foundation of Walsh analysis, and first- and second-order system analyses by Walsh technique. It also describes the Walsh domain operational method and how it is applied to linear system analysis